2012
DOI: 10.1021/ma300972v
|View full text |Cite
|
Sign up to set email alerts
|

Linear-Hyperbranched Graft-Copolymers via Grafting-to Strategy Based on Hyperbranched Dendron Analogues and Reactive Ester Polymers

Abstract: The synthesis of hyperbranched polyglycerol dendron analogues with precisely one focal amino functionality (H 2 N-hbPG) and their use for the synthesis of linear-hyperbranched graftcopolymers in a grafting-to approach is reported. By use of N,Ndibenzyl tris(hydroxylmethyl) aminomethane as a novel initiator for the ring-opening multibranching polymerization of glycidol, dendron analogues with one focal amino functionality of molecular weights ranging from 500 to 15000 g mol −1 and narrow to moderate polydispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
51
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 40 publications
(54 citation statements)
references
References 45 publications
2
51
0
1
Order By: Relevance
“…91,92 This makes the PPM approach effective for structure−property relationship studies of those biologically active polymers under physiological conditions. Frey et al 93 reported the synthesis of linear-hyperbranched graft-copolymers of polyHPMA via "grafting-to" approach by sequential modification of polyPFPMA backbone with a dendritic amine followed by 2-hydroxypropylamine. In a slightly different strategy, they synthesized polyHPMA with pendent β-cyclodextrin via triple PPM of polyPFPMA obtained by RAFT.…”
Section: Controlled Radical Polymerization For Homopolymers and Statimentioning
confidence: 99%
“…91,92 This makes the PPM approach effective for structure−property relationship studies of those biologically active polymers under physiological conditions. Frey et al 93 reported the synthesis of linear-hyperbranched graft-copolymers of polyHPMA via "grafting-to" approach by sequential modification of polyPFPMA backbone with a dendritic amine followed by 2-hydroxypropylamine. In a slightly different strategy, they synthesized polyHPMA with pendent β-cyclodextrin via triple PPM of polyPFPMA obtained by RAFT.…”
Section: Controlled Radical Polymerization For Homopolymers and Statimentioning
confidence: 99%
“…Subsequently, the PEG or hb PG side chains were introduced at the reactive PFPA block by a grafting‐to approach using their monoamino derivatives resulting in poly( para ‐(2,5‐bis pentyloxy)phenylene vinylene)‐ block ‐poly(poly(ethylene glycol) acryl amide) (BPO‐PPV‐ b ‐P(PEG)AA) and poly( para ‐(2,5‐bis pentyloxy)phenylene vinylene)‐ block ‐poly((hyperbranched polyglycerol) acryl amide) (BPO‐PPV‐ b ‐P( hb PG)AA). PFPA is an excellent component for this strategy, since the reactive esters react selectively and quantitatively with amines without cross‐linking, despite the presence of multiple alcohols in hb PG . Studies of the polymers by transmission electron microscopy (TEM) in various solvents revealed different self‐assembled structures, depending on the topology and the molecular weight of the polyether side chains.…”
Section: Resultsmentioning
confidence: 99%
“…For the synthesis of the graft copolymers with linear and hyperbranched side chains, P1 was reacted both with α‐methoxy‐ω‐amino polyethylene glycol (PEG‐NH 2 ) and hb PG dendron analogues with a single focal amino functionality ( hb PG‐NH 2 ), respectively in polymer modification reactions (Scheme and Table ). Commercially obtained PEG‐NH 2 with molecular weights (Mn) of 700 and 5000 g mol −1 was used to synthesize two graft copolymers ( P3 with PEG 750 and P4 with PEG 5000 ).…”
Section: Resultsmentioning
confidence: 99%
“…145 In this work, hyperbranched polyglycerol dendron analogs with a single focal amino functionality (H 2 N-hbPG) were attached to a reactive ester polymer (poly(pentafluorophenol methacrylate), PPFPMA) (Fig. 28).…”
Section: Linear-hyperbranched Graft Copolymersmentioning
confidence: 99%